2016
DOI: 10.1007/s40596-016-0536-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Career Outcomes of a Resident Academic Administrator, Clinician Educator Track: A Seven-Year Follow-up

Abstract: This study underscores the benefits of a clinician educator track and suggests areas for future growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… 14 In addition to exposure to a specific area of concentration, tracks may increase scholarly activity, academic success, and selection of a career in academic medicine. 14 16 Despite these potential benefits and suggested strategies for implementation, a recent review of publicly available data demonstrated that specialized tracks are not widespread in EM training programs. 14 , 17 The reasons for this are unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 14 In addition to exposure to a specific area of concentration, tracks may increase scholarly activity, academic success, and selection of a career in academic medicine. 14 16 Despite these potential benefits and suggested strategies for implementation, a recent review of publicly available data demonstrated that specialized tracks are not widespread in EM training programs. 14 , 17 The reasons for this are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These roles have been embraced by the profession, as evidenced by their inclusion as core competencies for physicians. [29][30][31] A few programs (e.g., tracks) that foster nonclinical interests in residency have been described [32][33][34][35][36][37][38] ; long-term program outcomes are largely unknown. For most trainees, residency does not allow for meaningful integration of clinical and nonclinical interests, despite recommendations in centennial reports to provide opportunities for trainees to experience diverse physician roles.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently there has been the advent of medical education tracks within graduate medical education across specialties (Psychiatry, Internal Medicine, Pediatrics, Family Medicine, Emergency Medicine, and Internal Medicine Fellowships). [3][4][5][6][7][8][9][10][11][12][13][14][15] A 2019 scoping review looking at these medical education tracks found that most included core curricula with classroom-based sessions and workplace-based opportunities to practice skills, and required scholarly projects. 15 Outcomes data published regarding these programs are sparse.…”
Section: Introductionmentioning
confidence: 99%